Black Box Testing for HIV AIDS Digital Counseling Website (D-Cohiva Apps) with State Transition Technique - Maryanti, Dwi; Pangesti, Annisa Rahayu; Suprihatiningsih, Trimeilia (Jurnal Penelitian Pendidikan IPA, 2023)
The Al-Irsyad University Cilacap lecturer team has created the Digital Counseling HIV/AIDS (D-Cohiva) website with the Software Development Life Cycle (SDLC) stages. The D-Cohiva website provides internet-based interventions on HIV/AIDS counseling that can be used anywhere and anytime. In general this study attemps to analyze the related inputs and outputs, as well as to determine the suitability of the actual conditions with the expected conditions and ensure the quality and functionality of the D-Cohiva website, black box testing with the state transition technique was conducted. The research method used by researchers is the descriptive-qualitative method, namely by collecting data, then analyzing and describing the results of their observations. The system testing technique used is the black box with state transition technique. The study obtained eight test cases with 100% success, in accordance with the expected results. Conclusion: The D-Cohiva website is feasible to use and guaranteed according to the desired function.